Active and restorative campus: designing a garden street for student’s mental and physical well-being - DeVault, J. Ross (Kansas State University, 2015)
A significant decline of mental and physical health exists within college students today (ACHA, 2014; Gallagher, 2006). Recently, to promote mental health, restorative landscapes have emerged as a trend in healthcare environments by formalizing the healing properties of nature within a designed environment. Humans have been shown to undergo a measurable relief of stress, improved attention, and an improved overall sense of well-being when exposed to a restorative landscape setting. Opportunities exist for university campuses to more advantageously employ the mental health benefits of restorative landscapes. Furthermore, to address physical health, the university campus holds unique opportunities to increase students’ physical activity through promotion of active lifestyles using active modes of transportation. Campus streets, based on their lack of affordances to promote mental and physical health as well as their inherent connectivity to key campus buildings and spaces are investigated as a site for a designed solution. A recent trend of campus street conversions to pedestrian malls is identified and explored as a tool to facilitate creation of a restorative and active campus. The project, based in two fundamental research questions, investigates how campus street design can improve the collective mental health of college students, and how campus street design can promote physical health. Literature review analysis reveals theories and principles of restorative landscape and campus design. The project unites these findings with case study analysis to form a framework to facilitate the design of restorative environments within a university campus. Pragmatic evidence of built environment interventions has been synthesized from literature review and case study analysis into an additional framework to increase physical activity through active transportation. Kansas State University’s campus has been identified as a suitable case for a design proposal. Planning and design decisions at three nested scales are made to illustrate how the frameworks may be applied to reclaim a campus street as an active and restorative “garden street.” In the context of declining mental and physical health among college students, the synthesis of principles related to restorative landscape design and active transportation presents a valuable structure to mitigate declining mental and physical health of students.
Keywords: Landscape architecture; Student health; Restorative landscapes; Active transportation; Transportation planning; Campus design; Landscape Architecture (0390); Public Health (0573); Transportation (0709)